2017
DOI: 10.1016/j.ecolecon.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating demand for perennial pigeon pea in Malawi using choice experiments

Abstract: Perennial crops have numerous ecological and agronomic advantages over their annual counterparts. We estimate discrete choice models to evaluate farmers' preferences for perennial attributes of pigeon pea intercropped with maize in central and southern Malawi. Pigeon pea is a nitrogen-fixing leguminous crop, which has the potential to ameliorate soil fertility problems related to continuous maize cultivation, which are common in Southern Africa. Adoption of annual pigeon pea is relatively low but perennial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…Our results are consistent with other studies that considered high yields, resistance to diseases, and lower price as main drivers for selecting improved seeds (Asrat et al, 2010;Sibiya et al, 2013;Waldman et al, 2017).…”
Section: Resultssupporting
confidence: 83%
“…Our results are consistent with other studies that considered high yields, resistance to diseases, and lower price as main drivers for selecting improved seeds (Asrat et al, 2010;Sibiya et al, 2013;Waldman et al, 2017).…”
Section: Resultssupporting
confidence: 83%
“…Waldman et al. () evaluated Malawian farmers’ preferences for perennial pigeon pea to assess the tradeoffs involved in annual versus perennial pigeon pea production. Similarly, Birol et al.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal compatibility of maize and soybean has been observed previously by Agyare et al (2006), Snapp et al (2002), andvan Vugt et al (2018). Evidence from a logit link analysis of crop preference in central Malawi revealed that female farmers in particular express strong interest in producing and marketing soybean and generally have access to improved soybean seed (Waldman et al, 2017). Taken together, there are multiple lines of evidence that soybean rotated with maize is a farmer-preferred treatment with high adaptation to weather and edaphic variability.…”
Section: System Stability and Adaptationmentioning
confidence: 53%